Sharia Governance and Sustainability Reporting: The Mediating Role of Financial Performance - Falikhatun, Falikhatun; Wahyuni, Salamah; Nilasakti, Afifah Oki; Niswah, Milanda Ainun (al-Uqud : Journal of Islamic Economics, 2020)
Using a sample of registered Sharia Commercial Banks (BUS) in Indonesia during 2014-2017, we examine the effect of Sharia Governance on Sustainability Reporting with financial performance as a mediating variable. Our results support the idea that sharia governance (sharia supervisory board, independent commissioner, board of director's meeting and audit committee) has significant influence on the sustainability reporting. Further analysis indicates the mediating role of financial performance in the relationship between sharia governance and sustainability reporting. Our results suggest that it is essential for regulatory agencies to enhance the supervision role of independent commissioners.